The effects of degrees of support for learner independence through web-based instruction and levels of general english proficiency on english reading comrehension ability of second year undergraduate learners - Rosukhon Swatevacharkul (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006